1979
DOI: 10.2307/1129421
|View full text |Cite
|
Sign up to set email alerts
|

Smooth-Pursuit Eye Movements in the Newborn Infant

Abstract: The capacity of newborn infants to smooth-pursuit eye movements in single-target tracking and in optokinetic nystagmus to a moving striped field was examined utilizing DC electrooculography. Smooth-pursuit movements were observed in all infants who were alert during testing, but they occupied less than 15% of viewing time during single-target tracking. The velocity of smooth-pursuit segments in single-target tracking increased linearly to a target velocity of 19 degrees/sec and deteriorated rapidly at faster s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Smooth Pursuit Smooth pursuit has been elicited in newborns (Kreminitzer et al 1979, Shea & Aslin 1990) under conditions in which target speeds are moderately slow and velocity is constant (see Hainline 1998). A rapid improvement in smooth pursuit performance apparently occurs between birth and 3-4 months of age (Aslin 1981, Phillips et al 1997, Von Hofsten & Rosander 1997.…”
Section: The Development Of Spatial Orientingmentioning
confidence: 99%
“…Smooth Pursuit Smooth pursuit has been elicited in newborns (Kreminitzer et al 1979, Shea & Aslin 1990) under conditions in which target speeds are moderately slow and velocity is constant (see Hainline 1998). A rapid improvement in smooth pursuit performance apparently occurs between birth and 3-4 months of age (Aslin 1981, Phillips et al 1997, Von Hofsten & Rosander 1997.…”
Section: The Development Of Spatial Orientingmentioning
confidence: 99%
“…In visually normal adult humans, monkeys, and cats, horizontal OKN is symmetrical-the alternating pursuit and saccadic eye movements are similar whether the stimulus moves leftward or rightward and whether subjects look with one eye or both (e.g., Braun & Gault, 1969;Lewis, Maurer, Smith, & Haslip, 1992;Pasik & Pasik, 1964). When tested binocularly, even newborn babies, like young monkeys and kittens, show symmetrical OKN in response to horizontally moving patterns (Atkinson, 1979;Krementizer, Vaughan, Kurtzberg, & Dowling, 1979;van Hof-van Duin, 1978). In contrast, when tested monocularly, all three species show asymmetrical OKN during early infancy: OKN is elicited easily when a pattern moves temporally to nasally, but not when it moves nasally to temporally (e.g., Atkinson, 1979;Lewis, Maurer, Smith, & Haslip, 1992;van Hof-van Duin, 1978).…”
Section: Asymmetry Of Optokinetic Nystagmus Normal Developmentmentioning
confidence: 99%
“…Infants are known to have mechanisms for detecting motion, separating moving regions from a stationary background, and tracking a moving region (22,23). However, our simulations showed that general motion cues on their own are unlikely to provide a sufficiently specific cue for hand learning: the extraction of moving regions from test video sequences can yield a low proportion of hand images, which provides only a weak support for extracting the class of hands (SI Results and Fig.…”
mentioning
confidence: 91%